STRATEGI MANAJEMEN KEUANGAN DALAM MENINGKATKAN MUTU PENDIDIKAN DI SEKOLAH TINGGI ILMU TARBIYAH IQRA’ KAPUAS HULU KALIMANTAN BARAT - Syamsiah Syamsiah (CV. Adiba Aisha Amira, 2023)
A university is an institution of higher education and research that provides academic degrees in various fields. The degree obtained can certainly guarantee the quality of a person's education. To achieve good quality, of course a university must be able to provide the facilities and infrastructure as well as the standards needed to achieve good quality education. In this case, of course every university cannot be separated from funds. These funds are the main spearhead in the implementation of existing programs. Likewise, the Tarbiyah Iqra' Kapuas Hulu College of Science must also be able to have a good strategy in financial management. Therefore, every university must pay attention to financial management strategies in improving the quality of education. The focus of this research is: 1) How is the planning, implementation and financial evaluation at the Tarbiyah Iqra' Kapuas Hulu College of Science? 2) What is the financial management strategy for improving the quality of education at the Tarbiyah Iqra' Kapuas Hulu College of Science? This research uses a qualitative approach and a field study type. Data collection techniques through interviews, observation and documentation. Data analysis uses data collection models, data reduction, data display and data verification/drawing conclusions. The research results show the following: 1) Planning, implementation and financial evaluation at the Tarbiyah Iqra' Kapuas Hulu College of Science have been carried out in accordance with existing procedures. However, there are still things that have not been implemented. For example, there is no financial transparency yet and there are no guidelines for accountability reports, 2) The financial management strategy implemented is considered to meet educational quality standards. However, until now the Tarbiyah Iqra' Kapuas Hulu College of Science has not implemented investment costs, and has not budgeted financially for lecturers to increase competency qualifications.